PREVALENCE OF SCHISTOSOMA NASALE IN CATTLE IN CAUVERY DELTA REGION OF TAMIL NADU - M.K. Vijayasarathi; A. Latchumikanthan; A. Meenakshisundaram (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Nasal washings and faecal samples were collected from 110 cows during the period between July 2019 and June 2020 in and around the Orathandu, Cauvery delta zone of Tamil Nadu to document the seasonal prevalence of Schistosoma nasale and Schistosoma spindale. These samples were processed and screened by using the standard parasitological techniques. Out of 110 nasal washings, 23 samples (20.9%) confirmed the Schistosoma nasale infection by the presence of eggs. No faecal samples could be detected positive for Schistosoma spindale infection during the study period